Genomic Characterization of Streptococcus suis Serotype 24 Clonal Complex 221/234 From Human Patients - Kerdsin, Anusak; Hatrongjit, Rujirat; Wongsurawat, Thidathip; Jenjaroenpun, Piroon; Chopjitt, Peechanika; Boueroy, Parichart; Fittipaldi, Nahuel; Zheng, Han; Gottschalk, Marcelo (Frontiers in Microbiology, 2021)
Streptococcus suis is a zoonotic pathogen that causes invasive infections in humans and pigs. Although S. suis serotype 2 is prevalent among patient and swine infections, other serotypes are occasionally detected in humans. Of these, serotype 24 clonal complex (CC) 221/234 are recognized as emerging clones of human infection. Genomic exploration of three S. suis serotype 24 CC221/234 strains revealed antimicrobial resistance genes, pathotyping, virulence-associated gene (VAG) profiles, minimum core genome (MCG) typing, and comparison of the genomes. Based on these analyzes, all three serotype 24 strains were MCG7-3 and should be classified in the intermediate/weakly virulent (I/WV) group. All selected serotype 24 strains were susceptible to several antibiotics including -lactam, fluoroquinolone, and chloramphenicol. Resistance to tetracycline, macrolide, and clindamycin was observed and attributed to the genes tet(O) and erm(B). Genomic comparison revealed the strains S12X, LSS66, LS0L, LS0E, 92-4172, and IMT40201 that had phylogenetic affinity with serotype 24 CC221/234. Analysis of 80 virulence-associated genes showed that all three serotype 24 strains lacked 24 genes consisting of adhesin P, epf, hyl, ihk, irr, mrp, nadR, neuB, NisK/R, ofs, permease (SSU0835), rgg, revS, salK/R, sao, sly, spyM3_0908, srtBCD, srtF, srtG, SSU05_0473, virA, virB4, and virD4. Eleven specific sequences were identified in the 3 serotype 24 genomes that differed from the genomes of the representative strains of epidemic (E; SC84), highly virulent (HV; P1/7), I/WV (89-1591), and avirulent (T15 and 05HAS68).